Advancing Cancer Vaccine Development through CRISPR/Cas9 Technologies and Future Opportunities - Mohammad Nadeem Khan (International Journal of Vaccines, 2025)
The advent of CRISPR/Cas9 genome editing has revolutionized the cancer immunotherapy market, offering unprecedented precision and versatility in the development of next-generation cancer vaccines. This review examines how CRISPR technologies are being integrated into various stages of cancer vaccine development including neoantigen discovery, dendritic cell engineering, cancer cell reprogramming, and tumor microenvironment modulation. In the area of neoantigen discovery, CRISPR enables rapid identification and validation of tumor-specific mutations, thereby supporting the design of highly personalized vaccines. Engineered dendritic cells, generated through CRISPR-based modifications, demonstrate improved antigen presentation and enhanced activation of T-cell responses. Similarly, reprogramming of cancer cells using targeted gene editing facilitates the development of whole-cell vaccines with increased immunogenicity. Beyond individual cell manipulation, CRISPR also provides opportunities to reshape the tumor microenvironment by knocking out immunosuppressive pathways or introducing immune-stimulatory factors, thereby improving vaccine potency. Newer CRISPR systems, including Cas12 and Cas13, along with advanced strategies such as CRISPRa/i and multiplex gene editing, broaden the scope of cancer vaccine design, offering refined control over gene expression and multi-targeted approaches. The choice of delivery platforms including lipid nanoparticles, viral vectors, electroporation, and exosome-based carriers further influences clinical applicability. Importantly, several ongoing clinical trials are already testing CRISPR- based cancer immunotherapies, underscoring the translational potential of these technologies. Despite promising results, challenges remain, including off-target effects, immunogenicity, ethical issues, and regulatory barriers. Finally, we present future directions, including CRISPR- guided nanotumors and AI-driven neoantigen prioritization, which together highlight the importance of CRISPR.
Keywords: CRISPR/Cas9; Cancer vaccines; Gene delivery systems; Neoantigen discovery; Tumor microenvironment; precision oncology